A single bout of aerobic exercise modulates motor learning performance and cortical excitability in humans - Kuo, Hsiao-I; Hsieh, Ming-Hsien; Lin, Yi-Ting; Kuo, Min-Fang; Nitsche, Michael A. (International journal of clinical and health psychology, 2023)
Evidence indicates beneficial effects of aerobic exercise on motor learning performance, which might be caused by the impact of aerobic exercise on cortical excitability. It is thus suggested that physiological effects of aerobic exercise on cortical excitability determine the effects of aerobic exercise on motor learning. Nevertheless, respective results usually come from independent studies, and a prove of the causal relationship between neurophysiological and motor learning effects is still missing. This study aims to explore the impact of a single bout of aerobic exercise on brain physiology and motor learning, and the association between these phenomena in humans The study was conducted in a cross-over design. In twenty healthy subjects, cortical excitability and motor learning were assessed before and after a single bout of aerobic exercise or a control intervention The results show that aerobic exercise improved motor sequence learning and enhanced cortical excitability in humans. Furthermore, a correlation between the exercise-dependent alteration of cortical excitability (short intracortical inhibition, which is determined primarily by the GABAergic system) and improvement of motor learning has been found The study found motor learning performance-improving effects of aerobic exercise, and these results might be explained by an exercised-caused alteration of cortical excitability, especially a reduction of GABA activity.